Study on Effect of Different Operating Parameters on Francis Turbine Noise - Singh, Rajbir (My University, 2010)
In our modern, rapidly expanding environment one of the developing problems is that of noise. Apart from the pure annoyance factor of noise, exposure to an intense sound field over a long period of time presents the risk of permanent damage of hearing. Sound may be described as the disturbance that propagates through a physical (elastic) medium. Rather noise can be conveniently and concisely defined as unwanted sound. With the rise in population which has lead to increase in traffic and industries one of the developing problems is of “Noise”. In the modern day to day world one of the basic needs is for energy generation in order to cope with rise in demands of electricity. For generation of electric energy it is necessary to run turbines. Running of turbines creates a lot of noise which pollutes our environment and leads to detrimental effects on neuroendocrine, cardiovascular, respiratory and digestive systems. Chronic exposure to noise causes fatigue and interferes with concentration, thus reducing work efficiency. With ever increasing consumption of electricity, it is a matter of concern for our country to control the noise pollution due to it and act for the savage of environmental hazards which can be caused due to it. Public at large scale is raising concerns over the declining state of environment and health. Most of the electricity is generated by hydro turbines. In the present study the hydro turbine chosen for work is Francis turbine because it is used in energy generation plants and set up was available in the labortary. Turbine set up can be distributed into two units on the basis of noise generation, active noise and passive noise. Components that generate active noise are turbine unit and for passive noise are pumping system, etc. Passive noise propagates from pump, motor, coupling and bearings, etc. In the present study an attempt has been made to fabricate a acoustic enclosure to control the passive noise from the pumping unit. In this regard an acoustic enclosure was functionally designed and polyurethane form was used on the surfaces of the enclosure. An attempt has also been made to measure noise impact at points A, B, C, D, E (at a distance of 0.5 m meter surrounding the turbine). It has been figured out that using acoustic enclosure noise reduces to considerable levels near the A, B, C, D and E points surrounding the turbine in comparison to noise generated by setup without enclosure. The effect of enclosure on 1-1 octave band frequency analysis has also been studied in order to figure under which frequency, sound pressure level is high and enclosure is effective for which frequency range. All these studies have been done by varying vane openings, loads and speeds at the marked locations from the turbine.
Keywords: Different Operating Parameters; Francis Turbine Noise